ARTS AND CRAFTS CURRICULUM AT PUBLIC SCHOOLS OF PAKISTAN - Huma, Afshan; Rizwan, Sidra; Rafiq, Rizwana (Journal of Arts & Social Sciences, 2024)
In a country where generations have been indoctrinated via biased and filtered information in the curriculum; this study was found to be a significant addition to the local narrative and discourse of education and curriculum planning. School curriculum around the world includes arts and crafts especially at the elementary school level. Here the researchers have explored the dimension of education which can add something locally profitable and that may be acceptable for the planners who are willing to develop a curriculum that is meaningful and useful for skill development among student. The study at hand is a step towards a curriculum reform to develop the skill-set that is culturally grounded, so that it may not be considered either irrelevant or labeled as a foreign agenda. The researchers’ assumption is that Pakistan being a country of various land resources, climate, and cultures, could develop a unique model of wholesome economy; if the local arts and crafts turn into globally marketable product; but for that it is important to bring the right skills set in the curriculum. The researchers conducted a mixed method study with an ethnographic approach in Rawalpindi district using a lens of skill based entrepreneurship education to identify the local arts and crafts which may be offered and included in the curriculum of secondary schools. The findings of this study informed how the curriculum could be reformed if it is based on experiential learning of local arts and crafts.